Balancing subsidiary influence in the federative MNC: a business network view - Andersson, Ulf; Forsgren, Mats; Holm, Ulf (Journal of International Business Studies, 2007)
In this paper, we argue that a fruitful approach to the analysis of inter-organisational power in multinational corporations (MNCs) is to model the organisation as a federation. In the federative MNC, the headquarters and the subsidiaries are involved in a perpetual bargaining process. Thus a crucial issue is what power bases are there that the different actors in the federative MNC can use to influence strategic decisions. In this paper, we focus on the power bases associated with the local business network in which the different subsidiaries are embedded, and on the headquarters’ knowledge concerning these networks. A causal model is developed and tested with data from 97 subsidiaries in 20 MNC divisions. The results indicate that the strength and influence of a subsidiary's local business network are determined by the extent to which the subsidiary provides technology within the MNC. The fact that the business network is strong does not suffice to augment the intra-organisational power of a subsidiary. In addition, our investigation also provides support for the idea that, when the headquarters has a sound knowledge of the subsidiaries’ business networks, it is better able to balance or moderate the influence of strong subsidiaries. The paper concludes by pointing out a potential dilemma facing the headquarters of the federative MNC: externally embedded subsidiaries can provide access to a variety of competencies, but they may also reduce the subsidiaries’ interest in contributing to the overall performance of the MNC.